Legal Analysis Of The Effectiveness Of Disciplinary Punishment Enforcement In Improving The Discipline Of State Civil Apparatus: Research Study Of The Port Master And Special Port Authority Office (KSOP) Batam - Ngatemi Ngatemi; Erniyanti Erniyanti; M. Soerya Respationo; Dahlan Dahlan; Parameshwara Parameshwara (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Enforcement of discipline among the State Civil Apparatus (ASN) is an important component in maintaining professionalism and efficiency of public services. This study aims to analyze the effectiveness of disciplinary punishment enforcement in improving ASN discipline at the Batam Municipal and Special Port Authority (KSOP) Office. The background of this research includes various challenges in enforcing ASN discipline, such as long and bureaucratic procedures, low awareness of discipline, and political intervention. The research method used is normative juridical using secondary data through library research, and also an empirical juridical approach with primary data through field research. Primary data collection was carried out through in-depth interviews, observations, and document analysis. The research respondents consisted of Batam KSOP employees, related officials, and other parties related to discipline enforcement in the environment. The results of the study show that the effectiveness of disciplinary enforcement in KSOP Batam is still not optimal. Convoluted enforcement procedures, lack of employee understanding of the importance of discipline, and political intervention were the main obstacles found. In addition, limited human resources and facilities also hinder the effective discipline enforcement process. This study also found that efforts to simplify procedures, increase socialization and education, and strengthen transparent supervision can increase the effectiveness of disciplinary punishment enforcement. Suggestions include the need for bureaucratic reform to simplify discipline enforcement procedures, the implementation of training and education programs on an ongoing basis, and the establishment of an independent internal oversight unit. Additionally, it is important for governments to ensure that discipline law enforcement is free from political interference and supported by adequate resources. With these steps, it is hoped that the discipline of ASN at KSOP Batam can be improved, which will ultimately contribute to improving the quality of public services and the reputation of government agencies.